Utilization of Crabs Shell (Portunus pelagicus) as Sources of Calcium and Phosphorus in Making of Crackers Product - Vita Yanuar; Joko Santoso; Ella Salamah (Jurnal Pengolahan Hasil Perikanan Indonesia, 2009)
Crabs shell is main waste product from pasteurization or canning industry of crabs. It contains high minerals content especially Ca and P. The objectives of this experiment were to produce crabs shell powder through two methods i.e. dry and wet methods and to evaluate their physicochemical characteristics include solubility of Ca and P. Production methods of crabs shell powder did not significantly affected the physicochemical properties; however, wet method produced slightly higher solubility of Ca and P than dry method. Crabs shell powder addition in different concentrations (0, 0.75, 1.50, 2.25, and 3.00%) into crackers product did not affect  significantly sensory parameters through scoring test, therefore the smallest and the highest concentration of crabs shell powder addition, namely formulas A and D, were chosen to be tested for their physicochemical properties. Formula D crackers obtained high number of Ca and P and significantly different from other formulas include commercial product, however formula A crackers had the highest solubility of Ca and P with values were 42.12% and 57.08% respectively.Keyword: calcium crackers, phosphorus, solubility, shell powder, crabs